The Effect of Digital Game-Based Learning on Students’ Problem-Solving Skills in The Context of Sustainable Organic Farming - Emilia Candrawati; Silvia Syeptiani; Arsela Eko Listiono (Jurnal Zarah, 2026)
This study aims to implement the Digital Game-Based Learning (DGBL) model through the EcoFarm Challenge educational game to improve students' problem-solving skills. This research uses a research and development (R&D) approach combined with a quasi-experimental design and a one-group pretest-posttest design involving 18 students. Data analysis was performed using the Shapiro–Wilk normality test and the Wilcoxon Signed-Rank Test. The results showed that the data were not normally distributed (p < 0.05), so the Wilcoxon test was used. The test results showed a significant difference between the pretest and posttest (Z = -2.312; p = 0.021) with a large effect size (r = -0.788). Data visualization using a raincloud plot also showed an upward trend in scores despite individual variation. These results indicate that the DGBL model is effective in improving students' problem-solving skills through interactive, simulation-based learning experiences.